The role of social capital and collective actions in natural capital conservation and management - Auer, Alejandra Denise; Von Below, Jonathan; Nahuelhual, Laura; Mastrángelo, Matias; Gonzalez, Aira Edith; Gluch, Mariana; Vallejos, María; Staiano, Luciana; Laterra, Pedro; Paruelo, José (Elsevier, 2021)
The relationships among social capital (SC) and collective actions (CA) for nature conservation and management were analyzed across five case studies characterised by specific land-use dynamics in the South American continent. Data on SC and CA were obtained through a semi-structured questionnaire to groups of selected social actors. Multivariate statistical analysis was used to identify SC components and to evaluate SC across actors and cases. The results reaffirm that: i) the multidimensional nature and complexity of SC; ii) Higher levels of SC are related to higher levels of CA; iii) social actors with developed internal and external SC can better counter adverse conditions through CA compared to actors who only have one type of SC; iv) vulnerable social actors do not necessarily have a higher SC or engage in more CA, despite their higher dependence on natural resources; v) those who hold more power or influence in the territory, have higher levels of SC and CA; vi) vulnerable actors often carry out civil/community, economic and judicial actions, while dominant and structuring actors carry out more educational/technical and political actions. Therefore, the formation and maintenance of SC of the most vulnerable actors and those who support them must be a priority for political action, in order to counteract the asymmetric power relations that lead to the exclusion and marginalization of many rural actors.